The Zeta Potential in Crude Extracts of Some Hibiscus Plants for Water Treatment - Jones, A. N. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
The aim of this study was to investigate the coagulation mechanism and turbidity removal potential of some members of the Hibiscus family namely; Okra crude extract (OCE), Sabdariffa crude extract (SCE) and Kenaf crude extract (KCE) in treating both river water and synthetic kaolin water samples. Experiments were conducted in a series of batch tests using standard jar test apparatus and a Zeta sizer Nano particle analyser. The results show that while the coagulation mechanism of the extract in treating synthetic kaolin water was likely due to charge neutralisation and bridging action, in the river water it was by adsorption and bridging effect caused by raw water constituents. In addition, turbidity removal performance in synthetic kaolin water sample was 94, 88 and 85% using OCE, SCE and KCE respectively. Similarly, the efficiency of OCE, SCE and KCE in treating river water was observed to be excellent, achieving 98, 96 and 83% respectively. Overall, the coagulation mechanism and residual turbidity in water treated using Hibiscus seed extracts could be a feasible alternative to the conventional chemical to provide rural people with clean water in developing countries.